Angiographic biomarkers are significant predictors of treatment response to intravitreal aflibercept in diabetic macular edema - Martin Hein; Aleksandar Vukmirovic; Ian J. Constable; Vignesh Raja; Arman Athwal; K. Bailey Freund; Chandrakumar Balaratnasingam (Scientific Reports, 2023)
Abstract This prospective single-center study aims to identify biomarkers that predict improvement in best-corrected visual acuity (BCVA) and central retinal thickness (CRT) at 6 months, in 76 eyes with diabetic macular edema (DME) treated monthly with intravitreal aflibercept. At baseline, all patients underwent standardized imaging with color photography, optical coherence tomography (OCT), fluorescein angiography (FA) and OCT angiography (OCTA). Glycosylated hemoglobin, renal function, dyslipidemia, hypertension, cardiovascular disease and smoking were recorded. Retinal images were graded in a masked fashion. Baseline imaging, systemic and demographic variables were investigated to detect associations to BCVA and CRT change post aflibercept. Predictors of BCVA improvement included greater macular vessel density quantified using OCTA (p = 0.001) and low-density lipoprotein (LDL) ≥ 2.6 mmol/L (p = 0.017). Lower macular vessel density eyes showed a significant reduction in CRT but no BCVA improvement. Predictors of CRT reduction included peripheral non-perfusion seen on ultrawide-field FA (p = 0.005) and LDL ≥ 2.6 mmol/L (p < 0.001). Retinal angiographic biomarkers derived from OCTA and ultrawide-field FA may help predict functional and anatomic response to anti-vascular endothelial growth factor (VEGF) therapy in patients with DME. Elevated LDL is associated with treatment response in DME. These results may be used to better-select patients who will benefit from intravitreal aflibercept for treatment of DME.